Managing open school units amid COVID-19 pandemic through the experiences of Greek principals: Implications for current and future policies in public education - Eleftheria Spyropoulou; Theodore Koutroukis (Administrative Sciences, 2021)
The purpose of this study was to examine the experiences of primary and secondary Greek school principals, regarding the management of their school units at the beginning of the school year 2020-2021, amid the COVID-19 pandemic. A qualitative study of 57 principals was undertaken, in order to explore the following questions: (a) What were the difficulties and obstacles that principals faced during the management of the school unit from the beginning of the school year? (b) What factors helped them to manage these difficulties? Written answers were analyzed using thematic analysis. Several key findings emerged, indicating that, in general, the principals had to respond to an unprecedented crisis context, under tremendous pressure, with limited resources. They faced a variety of difficulties, both on a personal level and in the context of their professional role. They also encountered difficulties above their role, which had to do with the general impact of the extended sanitary crisis on the emotional state and perceptions of the members of the school community. The results of the research have implications for the policy that is applied in schools in the context of the COVID-19 pandemic.
Keywords: 350; COVID-19; Greece; leadership; principals; public education; school management